Prilaku Organisasi Tenaga Kependidikan SMAN 1 Pulau Punjung Kabupaten Dharmasraya - DESNIATI, SISSI - (Pendidikan Sosiologi, 2014)
Education personnel on duty as a supporter of education process in schools. Although it served as a non-teaching education staff, staff uphold the values of education in charge of providing administrative services to support the implementation of the educational process at school, they are non-teaching staff on duty at the school which is often referred to as administrative (TU). In accordance with the subject matter, the research problem is formulated as follows: (1) How does the behavior organissai educators in SMAN 1 Arbor Island Dharmasraya? (2) What are the constraints faced by educators in carrying out its functions in SMAN 1 Arbor Island Dharmasraya?The approach used in this study is descriptive qualitative research type, research informants were taken by purposive sampling, informants in this study, researchers took a total of 18 people made up of, the head of administration, clerical employees, teachers and students of SMAN 1 Dharmasraya Arbor Island. The type of data are primary data and secondary data. Techniques and data collection tools used were observation, interview and documentation. Analysis of the data used is using Miles and Huberman models through three stages: data reduction, data presentation and conclusion.The results showed that the behavior of the organization of education personnel SMAN 1 Arbor Island Dharmasraya namely (1) No discipline or late arrival time, (2) Slacking off work, (3) Removing the responsibility, (4) Less polite or friendly in serve teachers and students, and the constraints faced by the employees of the administration: (1) lack of skill or ability clerical employees in carrying out its functions and (2) lack of infrastructure within the administration so that inhibition of the administrations employees in performing their duties.